Interaction between Perceived Usefulness and Self-Efficacy towards Sustainability of Sharia P2PL investment - Nurhidayah Nurhidayah; Mohamad Bastomi (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study aims to analyze whether there is influence of financial and technological self-efficacy in determining investment sustainability. To add complexity, perceived usefulness moderating variables are used to sharpen the influence on investment sustainability. Respondents are investors who invest through the sharia P2PL application with a total of 171 investors. The collected data were then analyzed using the Moderation Regression Analysis Technique or MRA. - The results of the study prove that financial and technological self-efficacy have an effect on investment sustainability, as well as perceived usefulness having a mediating role that strengthens the interaction of financial and technological self-efficacy on investment sustainability. - Islamic Commercial Banks in Indonesia suggest to improve the financial performance in accordance with sharia principles.